Qatar 2022 World Cup : designing a context-based decision-making approach - Abeza, Gashaw; O'Reilly, Norm; Boesen, Mads Quist; Braunstein-Minkove, Jessica R. (London : Human Kinetics, Inc., 2020)
The case presents a challenging decision that the new Fédération Internationale de Football Association (FIFA) President faced with the Qatar 2022 World Cup. Specifically, the issues surround the agreement that the President signed a year after his election with Qatar Airways and the allegations made against the 2022 World Cup host country, Qatar, for human rights violations and state-sponsored terrorism. Right after the allegation was made against Qatar, the President formed an advisory group to help prepare him to make a rational decision on the case. You have been appointed as the members of the advisory board that is tasked with investigating and making recommendations on the President's challenge of keeping his campaign promises of restoring FIFA's image and raising more money for the federation.
Originally Published InAbeza, G., O'Reilly, N., Boesen, M. Q., & Braustein-Minkove, J. R. (2020). Qatar 2022 World Cup: Designing a Context-Based Decision-Making Approach. Case Studies in Sport Management, 9(1), 7-11.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fédération internationale de football association -- Case studies; Public relations -- Case studies; Sports -- Public relations -- Case studies